Persepsi Calon Guru Terhadap Model E-Assessment Dalam Pembelajaran Fisika - Hairunisyah Sahidu; Gunawan Gunawan; Lovy Herayanti (Department of Physics Education, Universitas Mataram, 2019)
Assessment is an essential part of learning. The success of a lesson can be known from the results of the assessment carried out both in aspects of the process and product. Some problems related to conventional assessments have to find the right solution. One of them is through the use of computer technology in assessment, which can be used both online and offline in a model better known as e-assessment. The final goal of this research is to produce an e-assessment model that is oriented to the thinking ability of the physics teacher candidates. This research includes development research, using the DDD-E model, namely: decide, design, develop, and evaluate. This article discusses the responses of students and lecturers to the models that have been developed. Respondents gave a positive response to the development of this model. Student responses are at intervals of 86% to 94%, with excellent categories. This model has the opportunity to continue to be developed for evaluation effectively and efficiently.